Forgotten Transports to Latvia - Pribyl, Lukas (Czech Republic, 2008)
Verzio FF submission Duration: 01:26:00 In 1942, hundreds of Czech Jews are deported to Riga in Latvia. In an eerily empty, dilapidated, fenced-off and snowed-in part of town, they find pots on stoves, clothes on the floor, as if everyone left in a hurry. Then stones wrapped in paper are thrown over the wire by young men held in a cordoned-off section of the ghetto. The notes say: “You will all be killed, like our families. We are the last survivors.” Yet life continues. Some people are sent to the Salaspils camp, where only ruthless selfishness offers a slim chance of survival, but others cling together, steadfastly keeping “normality” amid atrocities. Children go to school past bodies hanging from the gallows. Boys play football on the ghetto square/execution ground. Teenagers fall in love at clandestine parties, almost literally “dancing on graves”… Edited from 270 hours of interviews shot in 20 countries over 10 years, the film dispels our notions of a “Holocaust documentary”. Employing no commentary or contemporary footage, only a minimalist montage of interviews and never-seen materials drawn from a vast array of sources, the narrow, personal points of view combine to paint a life-affirming picture of survival through luck, wisdom, ingenuity and sheer will, as well as form a depiction of the Holocaust “as we don’t know it”.